THE EFFECT OF PH VARIATIONS ON MAGNETIC PROPERTIES OF MAGNETITE SYNTHESIZED FROM IRON SAND - Wildan, Muhammad Waziz; Rusianto, Toto (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Magnetite has been successfully synthesized from iron sand using co-precipitation method with variations of pH levels. The iron sand was obtained from South Coast of Yogyakarta. The iron sand was separated using a permanent magnetic bar to obtain the magnetic mineral, which is used as raw material. The raw material was ball milled to reduce the particle size down to â‰¤ 74 mm. It was then dissolved and stirred in HCl 37% at 80 oC for 3 hours. The reaction yielded a solution consisting of FeCl2 and FeCl3, which is called as a master solution. Ammonium hydroxide (NH4OH) 20% was added to the master solution to obtain Fe-oxide precipitation. The precipitation process depended on the pH of the solution, so the pH of the solution was arranged using variations of NH4OH contents. The volume ratios of the master solution and NH4OH were A (2:1), B (1:1), C (1:2) and D (1:3), they were designated as samples A, B, C and D, respectively. Those various compositions yielded solutions with various pH levels, i.e. 5, 8, 10 and 11, respectively. The black powder precipitation was immediately formed during the reaction. The powders were analyzed using XRD. The magnetic properties were measured using vibrating sample magnetometer (VSM). TEM was used to observe the particle size. From the XRD, it was found that magnetite compound was found on the solution with pH level â‰¥ 8. Magnetic properties test show that Ms (saturation magnetization) is 43 emu/gr found on the solution with pH level of 8. TEM images show that the smallest particle size found on the solution B with pH level of 8. Magnetic Nanoparticles (MNPs) with superparamagnetic properties can be synthesized from iron sand.